Situation Report: Romania, 16 July 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania and the Moscow Summit Meeting Romania's Stance at the Madrid CSCE Meeting Modern Ways of Interfering in Domestic Affairs Governmental Reshuffle Changes in the Statutes of Socialist Organizations in Agriculture Double Standards Concerning Labor Rights of Youth